Two new species of Centris (Aphemisia) Ayala, 2002 from Colombia with a synopsis of the subgenus for the country (Hymenoptera: Apidae: Centridini) - Vivallo, Felipe; Vélez, Danny; Fernández, Fernando (Zootaxa, 2016)
A synopsis of the species of Centris subgenus Aphemisia Ayala in Colombia is presented. A total of six species were recognized: C. lilacina Cockerell, C. mocsaryi Friese, C. plumipes Smith and C. quadrimaculata Packard, including C. celadonia n. sp. and C. vallecaucensis n. sp., two new species described from the Departments of Huila and Valle del Cauca, respectively. Diagnoses, descriptions, information on geographical distribution and an identification key to all species are provided. The previously unknown male of C. plumipes is described for the first time.